Buffy the Vampire Slayer - Stuller, Jennifer K. (Fan phenomena., 2013)
"Few could have predicted the enduring affection inspired by Joss Whedon's television series Buffy the Vampire Slayer. With its origins in a script Whedon wrote for a 1992 feature film of the same name, the series far outpaced its source material, gathering a devoted audience that remains loyal to the show more than a decade after it left the airwaves. Heralded for its use of smart, funny and emotionally resonant narrative, subversive and feminist characterizations and unique approaches to television as an art form, the show quickly developed its own unique fan community, who built on existing narratives through fan fiction, media manipulation and performance. Fan Phenomena: Buffy the Vampire Slayer explores how this continued devotion is internalized, celebrated and critiqued. Featuring interviews with culture-makers, academics and creators of participatory fandom, the essays here are windows into the more personal and communal aspects of the fan experience. Essays from critical thinkers and scholars address how Buffy inspires the creation of, among other enduring artefacts of fandom, fan fiction, crafting, performance, cosplay and singalongs. As an accessible yet vigorous examination of a beloved character and her world, Fan Phenomena: Buffy the Vampire Slayer provokes a larger conversation about the relationship between cult properties and fandom, and how their interplay permeates the cultural consciousness, in effect contributing to culture through new narrative, academia, language and political activism"--Provided by publisher.